História Da Arte E Arte/Educação: Diálogos Possíveis Nos Educativos De Museus - Carneiro, Fernanda Da Silva [UNIFESP] (2017)
This research deals with the presence of the History of Art in the teaching of art, focusing on the museological space. The study focuses on an initial investigation into its insertion in museum education, in order to think about issues such as aesthetics, image reading, history and formal comparisons are contextualized and addressed. The research seeks to show a circulation of ideas in the history of art during educational visits, because we believe that art / education travels through different fields of study. In order to analyze the ideas listed, we chose the following museums: the Pinacoteca do Estado de São Paulo, the Museu de Arte Moderna, the Museu de Arte Contemporânea da Universidade de São Paulo and the Museu Lasar Segall.